Customizing possibilities of Croatian apiaries for organic production of honey regarding of the type of beehive - Puškadija, Zlatko; Štefanić, Ivan; Bubalo, Dragan; Kezić, Nikola; Dražić, Marica Maja (Acta Agraria Kaposváriensis, 2002)
The EU Regulation (2092/91) concerning the organic-biological agricultural production gives also a standards for the organic-biological production of honey. This Regulation sets a highest requests to the beekeepers regarding the type and construction of beehive, and for the ecological approach in the cur at ion of bees using natural substances and biotechnological methods. The large variety in types of beehives is an obstacle towards to cheaper and efficient constructive adaptability of beehives for the organic-biological production. Although there are many different types of hives at Croatian apiaries, with large differences in parameters, the Albert-Žnidaršić (AZ) with 49%, and Langstroth (LR) hives, with 45% prevails. Among these hive types there is a significant portion of hives characterised by no-standard parameters. More than hundred different parameters for the beehives are known in the EU countries, so, Apimondia recommends promotion of LR and Dadant parameters as a standard. It is obvious that by an effective constructive adaptability the organic-biological honey production is possible only on 40% of beehives in Croatia.